Testing mechanisms of development within a computational framework - Jones, Gary (1999)
Theories of development have proposed several mechanisms by which development occurs in children. The majority of the proposed mechanisms lack precise definitions, and are difficult to test individually whilst holding the effects of all other mechanisms constant. Implementing the mechanisms within a computational framework forces precision and enables the effect of each mechanism to be examined in isolation. A computational model of adult behaviour in a developmental task was created. The model included a range of the mechanisms proposed by theories of development, whereas previous computational models of development have examined very few mechanisms. The mechanisms were tested in the model both independently and in combination, with the results being compared against the behaviour of seven year old children on the task. The independent modifications showed that the behaviour of the model changes significantly for four mechanisms: strategy choice, strategy accuracy, capacity, and processing speed. The best mechanism (strategy accuracy), when applied to the adult model, matched seven out of nine regularities in the behaviour of seven year olds, including reaction time and errors. The combined modifications also matched seven year old children's behaviour. The results show that a range of developmental mechanisms can now be routinely tested and evaluated within a single computational model. The method of modifying computational models is an interesting way to examine the influences of developmental mechanisms, and therefore helps in answering "What develops in children?".